Domestication or foreignization: strategies adopted in the amateur subtitling of swearwords in American crime drama movies into Arabic - Khalaf, Abed Shahouth; Md Rashid, Sabariah (DSR Publishers, 2020)
The stigmatized nature of swearwords renders their intercultural transference a problematic issue in film subtitling. This is because cultures differ in their tolerance of swearwords specially when displayed in the media. Accordingly, subtitling translators need to carefully handle the sensitive issue of swearwords. However, although the choice of a particular strategy is influenced by different ideological, cultural and contextual factors, there is consensus that swearwords are either toned down or completely deleted. In light of this, this study attempts to identify the strategies adopted by Arab amateur subtitlers when rendering swearwords in American crime drama movies into Arabic. To achieve this objective, a corpus consisting of the scripts of two of these movies with high occurrence of swearwords and their subtitles in Arabic is collated. Moreover, in the analysis of the translation strategies adopted, Vermeer’s (1978/2000) Skopos theorie is utilized and Venuti’s (1995) model of ‘domestication’ and ‘foreignization’ is adopted to determine the overall subtitlers’ translation behavior whether oriented to the source text/culture or target text/culture. The findings of the study indicate that certain domestication translation strategies were adopted to abide by cultural norms in the target culture and certain foreignization strategies were adopted to preserve the spirit of the source text. However, the overall translation behavior was target culture oriented.